2022
DOI: 10.1111/iep.12438
|View full text |Cite
|
Sign up to set email alerts
|

Transient atrial inflammation in a murine model of Coxsackievirus B3‐induced myocarditis

Abstract: Atrial dysfunction is a relatively common complication of acute myocarditis, although its pathophysiology is unclear. There is limited information on myocarditis-associated histological changes in the atria and how they develop in time. The aim of this study therefore was to investigate inflammation, fibrosis and viral genome in the atria in time after mild CVB3-induced viral myocarditis (VM) in mice. C3H mice (n = 68) were infected with 10 5 PFU of Coxsackievirus B3 (CVB3) and were compared with uninfected mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In our study, LAEF was identified as the only functional parameter showing statistically significant recovery, whereas the improvement in LV function was not statistically significant. This finding may be the result of the involvement of LA in the inflammatory process of myocarditis, as demonstrated recently in a murine model with viral myocarditis [ 26 ]. However, it may also be due to a change in LV filling pressures, which was believed to be a determinant of the LA reservoir and pump strain that were measured by speckle tracking echocardiography [ 27 ].…”
Section: Discussionsupporting
confidence: 58%
“…In our study, LAEF was identified as the only functional parameter showing statistically significant recovery, whereas the improvement in LV function was not statistically significant. This finding may be the result of the involvement of LA in the inflammatory process of myocarditis, as demonstrated recently in a murine model with viral myocarditis [ 26 ]. However, it may also be due to a change in LV filling pressures, which was believed to be a determinant of the LA reservoir and pump strain that were measured by speckle tracking echocardiography [ 27 ].…”
Section: Discussionsupporting
confidence: 58%
“…The LA actively modulates left ventricular filling through its distinct phases [17,40,53]. Another hypothesis is that the direct involvement of the atria during myocarditis contributes to proarrhythmogenic remodeling of the atria [54]. Our results demonstrate that utilizing atrial and ventricular strain serves as helpful and supportive non-contrast CMR parameters for risk stratifying patients with myocarditis at risk of arrhythmic complications.…”
Section: Discussionmentioning
confidence: 71%
“…Subsequently, the homogenized solution was frozen three times at − 80 °C and centrifuged at 4 °C, and the supernatant was isolated for conducting tests. Following the instructions of the aspartate aminotransferase assay kit (Nanjing Jiancheng Bioengineering Institute, China) [ 29 ], we divided the samples into test and control wells, and simultaneously prepared standard concentration wells. After 30 min of reaction with the substrate solution, 20 min with the 2,4-dinitrophenylhydrazine solution, and 15 min with NaOH, the absorbance values were measured using a microplate reader at a wavelength of 510 nm.…”
Section: Methodsmentioning
confidence: 99%